Review of Differentiation and Proliferation of Primordial Germ Cells in Culture - Zohreh Makoolati; Majid Naghdi (Journal of Advanced Biomedical Sciences, 2011)
Primordial germ cells (PGCs) are highly specialized cell population that arises from the epiblast in vivo. There are three critical steps in the life cycle of these cells: 1-Specification 2-migration and proliferation 3-prenatal and postnatal sex specific development. Specification of germ cells in epiblast occurs due to signals secreted from extraembryonic tissues. Primordial germ cells are required for continuation and development of the species. Thus, differentiation and purification of these cells from different cell sources is valuable for research, genetical analysis of germ cell development, epigenetic eveluation and infertility treatment. The most important part in the germ cell differentiation includes optimum media selection, distinguishing and purification of differentiated cell. Several studies about in vitro PGC differentiation have been reported. In order to distinguish PGCs in vitro, specific markers which are expressed in these cells are used. Furthermore, functional ability of these cells for production of offspring can be employed for this purpose.